Canonical forms and conservation laws in linear elastostatics - Hatfield, G.; Olver, P.J. (Archives of Mechanics, 1998)
In this paper, we shall review earlier work on canonical forms in linear elasticity, and applications to the classification of conservation laws (path-independent integrals).